Donor–acceptor conjugates-functionalized aluminum phthalocyanines: Photophysical and nonlinear optical properties. (5th July 2020) - Xu, Rui; Li, Bolong; Ding, Jiale; Li, Wei; Zhang, Yunhe
Graphical abstract: Highlights: Donor–acceptor conjugates-functionalized aluminum phthalocyanines were successfully synthesized. Donor-acceptor structure effectively promotes the photoinduced intramolecular electron transfer process. The improved nonlinearity is ascribed to the efficient photoinduced intramolecular electron transfer effect. Abstract: Photoinduced electron transfer/energy transfer (PET/ET) plays a very important role in improving the nonlinear optical (NLO) response. AlPc-Aqn and HAlPc-Aqn with donor-acceptor (D-A) structure were prepared by grafting aluminum phthalocyanine (AlPc) and hyperbranched aluminum phthalocyanine (HAlPc) through anthraquinone axial covalent bonding. After the axial covalent connection, the formed D-A phthalocyanine materials enhance the PET/ET process between the phthalocyanine ring and the anthraquinone structure, which results in significant fluorescence quenching and effectively improves the material's NLO properties. The discrepancy of LUMO levels (ΔE) further confirms that both AlPc-Aqn and HAlPc-Aqn formed a D-A system. This effectively promotes the electron transfer between the anthraquinone and the phthalocyanine ring, performing enhanced NLO response. Furthermore, compared to AlPc-Aqn, the special three-dimensional structure of HAlPc-Aqn brings a more efficient PET/ET process and exhibits a larger nonlinear absorption coefficient.